DIGITAL ERA CONSUMERS: PREFERENCES AND CONCERNS (International Journal of Food and Nutritional Sciences, 2021)
Mass Media is the most popular tool in the present scenario. The technologies through which this communication takes place include a variety of outlets. Broadcast media transmit information electronically, via such media as film, radio, recorded music, or television. Digital media comprises both Internet and mobile mass communication. Internet media comprise such services as email, social media sites, websites, and Internet-based radio and television. Many other mass media outlets have an additional presence on the web, by such means as linking to or running TV ads online, or distributing QR Codes in outdoor or print media to direct mobile users to a website. In this way, they can utilise the easy accessibility and outreach capabilities the Internet affords, as thereby easily broadcast information throughout many different regions of the world simultaneously and cost-efficiently. Outdoor media transmit information via such media as AR advertising; billboards; blimps; flying billboards (signs in tow of airplanes); placards or kiosks placed inside and outside buses, commercial buildings, shops, sports stadiums, subway cars, or trains; signs; or skywriting. Print media transmit information via physical objects, such as books, comics, magazines, newspapers, or pamphlets. Event organizing and public speaking can also be considered forms of mass media.